The application of energy absorbing structures on side impact protection systems - Njuguna, James A. K. (Inderscience, 2011)
This paper presents a system to improve the protection to the occupants of a World Rally Championship Car in case of a side impact involving a tree collision using energy-absorbing structures. An outline of the immediate events after the car crash into a tree is provided followed by an analysis of a typical standard rollcage, then the design criteria and features of a carefully selected design concept. The design model is produced using solid modelling/I-DEAS 11 softwares and PAM-Crash is used for the simulations. The simulation results show that Side Impact Protection System (SIPS) is capable of absorbing and dissipating 98% of the energy of a 14 m/s impact involving a 0.2 m diameter tree